Optimal position control of a mobile manipulator for minimum energy - Varela-Aldás, José (2022)
This work presents the position control with energy optimization for a mobile manipulator and the proposal is based on the Pontryagin's Minimum Principle. The objective function is subject to the kinematic model of the robot with the non-holonomic motion constraint of the mobile platform and the boundary conditions as the desired parameters of the controller. The obtained differential equations are solved using the Shooting method to find the optimal co-states. The simulation performed shows that the position errors tend to zero and the control actions are optimized. Furthermore, these results are evaluated with respect to a control law based on the inverse kinematics of the robot. Finding that the minimum energy objective function is affected by the final time.